2020
DOI: 10.21037/atm-20-4281
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of 2019-nCoV receptor ACE2 expression in different tissues and its significance study

Abstract: Background: On March 11, 2020, the World Health Organization (WHO) officially announced that the coronavirus disease 2019 (COVID-19) had reached global pandemic status. Current studies have found that angiotensin-converting enzyme 2 (ACE2) is a cell surface receptor of the novel coronavirus that plays a vital role in the pathogenesis of COVID-19. It is of immense importance for the prevention of virus transmission and treatment to clarify the distribution and expression of ACE2 in various tissues and organs of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0
7

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(72 citation statements)
references
References 21 publications
1
54
0
7
Order By: Relevance
“…Evidence suggests that sex steroids can influence ACE2 expression in the respiratory tract, and that higher ACE2 levels may be causally related to increased COVID-19 severity [67][68][69][70][71]. However, studies investigating ACE2 expression in respiratory tract tissues by sex have not consistently shown higher expression in males, highlighting that levels of ACE2 may not fully explain the observed male bias in severe COVID-19 disease [55,[71][72][73][74]. While our data and several other studies demonstrate robust expression of ACE2 in the human placenta that may vary by gestational age [12,15,[17][18][19]75,76], few studies have evaluated sex-specific placental ACE2 expression, and these have reported conflicting results [78,79].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that sex steroids can influence ACE2 expression in the respiratory tract, and that higher ACE2 levels may be causally related to increased COVID-19 severity [67][68][69][70][71]. However, studies investigating ACE2 expression in respiratory tract tissues by sex have not consistently shown higher expression in males, highlighting that levels of ACE2 may not fully explain the observed male bias in severe COVID-19 disease [55,[71][72][73][74]. While our data and several other studies demonstrate robust expression of ACE2 in the human placenta that may vary by gestational age [12,15,[17][18][19]75,76], few studies have evaluated sex-specific placental ACE2 expression, and these have reported conflicting results [78,79].…”
Section: Discussionmentioning
confidence: 99%
“…ACE2 mRNA expression was reported also in hypothalamus and pituitary gland cells [ 50 ]. Moreover, in a previous study, SARS-CoV was detected in pituitary tissues from patients who died from SARS [ 51 ].…”
Section: Main Pituitary Manifestations Of Covid-19mentioning
confidence: 99%
“…These receptors are expressed on a broad range of tissue. The highest levels of ACE2 expression and activity were found at the small intestine, kidney, heart, salivary glands, testicles, and thyroid, whereas lower levels were observed in the brain, skin, pituitary, and skeletal muscles [17,18]. Thyroid follicular cells express ACE2 as suggested by direct molecular analysis of surgical samples of thyroid tissue [19], leading the gland to be susceptible to SARS-CoV-2 injury once the infection has occurred.…”
Section: Biochemical and Immunological Relationship Between Sars-cov-2 And Thyroid Glandmentioning
confidence: 99%